2021
DOI: 10.3390/ijms22126192
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Anthocyanins, Deoxyanthocyanins and Pyranoanthocyanins on the Modulation of Tyrosinase Activity: An In Vitro and In Silico Approach

Abstract: Tyrosinase is the central enzyme involved in the highly complex process of melanin formation, catalyzing the rate-limiting steps of this biosynthetic pathway. Due to such a preponderant role, it has become a major target in the treatment of undesired skin pigmentation conditions and also in the prevention of enzymatic food browning. Numerous phenolic-based structures from natural sources have been pointed out as potential tyrosinase inhibitors, including anthocyanins. The aim of the present study was to indivi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 52 publications
(76 reference statements)
1
2
0
Order By: Relevance
“…However, MM-PBSA calculations (Figure 7) indicate that there are ligand-copper interactions for 17, suggesting a competitive inhibition. Previous experimental studies with mushroom tyrosinase [50] indicate that 17 exhibit a competitive type of inhibition, thus supporting MM-PBSA results.…”
Section: Discussionsupporting
confidence: 78%
“…However, MM-PBSA calculations (Figure 7) indicate that there are ligand-copper interactions for 17, suggesting a competitive inhibition. Previous experimental studies with mushroom tyrosinase [50] indicate that 17 exhibit a competitive type of inhibition, thus supporting MM-PBSA results.…”
Section: Discussionsupporting
confidence: 78%
“…In consequence, kinetic studies revealed that cyanidin-3- O -glucoside acts as a competitive inhibitor for tyrosinase, with an inhibition constant of 40.31 ± 3.61 µM. In addition, molecular simulations demonstrated that the oxygen atom at ring A of cyanidin-3- O -glucoside can interact with the central Cu 2+ of the human tyrosinase enzyme with the lowest binding energy of −10.8 kcal/mol [ 37 ]. Although Lee et al reported that cyanidin-3- O -glucoside slightly reduced the activity of murine tyrosinase enzyme by comparison to arbutin as a positive control [ 38 ].…”
Section: Discussionmentioning
confidence: 99%
“…This effect was also recently explored using cyanidin- and malvidin-3- O -glucosides pure standards and also elderberry and red wine ACNs extracts [ 247 ]. Overall, most of the compounds were found to exhibit UV-filter capacity, attenuate the production of reactive oxygen species in human skin keratinocytes and fibroblasts and showed inhibitory activity of skin-degrading enzymes (Tyrosinase, elastase, hyaluronidase, and collagenase) in the absence of cytotoxic effects [ 247 , 248 ]. Considering the described features of these compounds, a formulation containing them would benefit from a dual function of photoprotection blended with an anti-aging effect.…”
Section: Potential Applicationsmentioning
confidence: 99%